2003
DOI: 10.1016/s0002-9440(10)63503-1
|View full text |Cite
|
Sign up to set email alerts
|

Nontransgenic Hyperexpression of a Complement Regulator in Donor Kidney Modulates Transplant Ischemia/Reperfusion Damage, Acute Rejection, and Chronic Nephropathy

Abstract: Complement activation during ischemia and reperfusion contributes to the development of tissue injury with severe negative impact on outcomes in transplantation. To counter the effect of complement, we present a strategy to deliver a novel complement regulator stabilized on cell surfaces within donor organs. The membrane-bound complement regulator is able to inhibit complement activation when the donor organ is revascularized and exposed to host-circulating complement. Application of this construct to donor ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 35 publications
3
90
0
Order By: Relevance
“…These epithelial cells express the central complement component C3 (18,35,36), which, when cleaved, leads to formation of the membrane attack complex C5b-9 and release of C5a (18,20). Both of these complement effectors stimulate proinflammatory responses in epithelial cells and infiltrating leucocytes and can mediate cell death (17,37,38).…”
Section: 8mentioning
confidence: 99%
“…These epithelial cells express the central complement component C3 (18,35,36), which, when cleaved, leads to formation of the membrane attack complex C5b-9 and release of C5a (18,20). Both of these complement effectors stimulate proinflammatory responses in epithelial cells and infiltrating leucocytes and can mediate cell death (17,37,38).…”
Section: 8mentioning
confidence: 99%
“…Studies in complement-deficient mice have shown that these mice are protected from renal failure after ischemia/reperfusion (I/R) (1,2), and that generation of the anaphylatoxin C5a (3) and the membrane attack complex (2) may contribute to the pathogenesis of ischemic ARF. Treatment with agents that inhibit the complement cascade at specific steps during the activation cascade has proven effective at ameliorating ischemic ARF (3,4). Determining the initiating mechanisms of complement activation after renal I/R is essential to the effective use of complement inhibitors for the treatment and prevention of ischemic ARF.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the complement regulator to function locally. Previous studies have shown Mirococept to localise to endothelial and epithelial cell surfaces once infused through the renal artery in rat and human donor kidneys [118,119]. This resulted in a decrease in IR injury and less chronic vascular injury in rat donor organs.…”
Section: Complement Regulatory Proteinsmentioning
confidence: 91%